2014
DOI: 10.2989/16085906.2014.961939
|View full text |Cite
|
Sign up to set email alerts
|

Mobile health for early retention in HIV care: a qualitative study in Kenya (WelTel Retain)

Abstract: Many people newly diagnosed with HIV are lost to follow-up before timely initiation of antiretroviral therapy (ART). A randomised controlled trial (RCT), WelTel Kenya1, demonstrated the effectiveness of the WelTel text messaging intervention to improve clinical outcomes among patients initiating ART. In preparation for WelTel Retain, an RCT that will evaluate the effect of the intervention to retain patients in care immediately following HIV diagnosis, we conducted an informative qualitative study with people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(104 citation statements)
references
References 32 publications
3
101
0
Order By: Relevance
“…A total of eleven studies were identified, including nine qualitative only studies [3240] and two mixed method studies [41, 42] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of eleven studies were identified, including nine qualitative only studies [3240] and two mixed method studies [41, 42] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the CASP quality assessment tool for qualitative studies, seven studies [3235, 37, 39, 40] were evaluated as having “minor” methodological limitations while the other four [36, 38, 41, 42] were evaluated as having “moderate” limitations (Table 3). …”
Section: Resultsmentioning
confidence: 99%
“…Following the success of the WelTel trial for improving adherence to ART, another study in Kenya is seeking to evaluate the efficacy of SMS for patient retention in Nairobi [11]. Qualitative analysis has shown promise for enabling early identification of problems, leading to timely problem solving that may improve retention and engagement in care during the first year of diagnosis [12]. The MORE CARE trial in Cameroon tested the efficacy of reminders on follow-up in care among children exposed or infected with HIV [13 & ].…”
Section: Key Pointsmentioning
confidence: 99%
“…Programs should explore ways to engage these individuals in care at the time of testing, particularly by providing culturally competent case management and supportive services. 24,25 Results of this study must be considered in the context of several limitations. This study represents a convenience sample of members of a social/sexual networking website for MSM, and all measures were self-reported.…”
Section: Discussionmentioning
confidence: 99%